2009
DOI: 10.5144/0256-4947.2009.207
|View full text |Cite|
|
Sign up to set email alerts
|

Black ant stings caused by Pachycondyla sennaarensis: a significant health hazard

Abstract: Several species of ants cause stings, but not all lead to allergic reactions. We present a series of cases of allergic reactions following insect bites or stings that presented to our emergency department and that were caused by the black samsum ant (Pachycondyla sennaarensis). Reactions ranged from mild allergic reactions to severe anaphylactic shock. Patients were treated with subcutaneous epinephrine 0.3 mg, intravenous methylprednisolone 125 mg, intravenous diphenhydramine HCl 50 mg, and intravenous normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 7 publications
0
13
1
Order By: Relevance
“…Allergic reactions due to black ant stings range from pain with local itching at the sting site to severe anaphylactic shock. AlAnazi et al (2009) showed that the diversity of manifestation and human response to black ant stings in four cases encountered in Al Riyadh, the capital city of Saudi Arabia, and three patients were adult females [49]. In contrast to our findings, lower prevalence of black ant induced anaphylaxis was reported in Saudi Arabia (3.2%) [14], and Singapore (12.9%) [50].…”
Section: Discussioncontrasting
confidence: 86%
“…Allergic reactions due to black ant stings range from pain with local itching at the sting site to severe anaphylactic shock. AlAnazi et al (2009) showed that the diversity of manifestation and human response to black ant stings in four cases encountered in Al Riyadh, the capital city of Saudi Arabia, and three patients were adult females [49]. In contrast to our findings, lower prevalence of black ant induced anaphylaxis was reported in Saudi Arabia (3.2%) [14], and Singapore (12.9%) [50].…”
Section: Discussioncontrasting
confidence: 86%
“…It is also found as an emerging health problem in the southeastern United States 45 26, 46 especially in the Eastern province of Saudi Arabia but not in the North and West 47 …”
Section: Distinct Regional Allergensmentioning
confidence: 99%
“…It has been monitored only in the urban and the rural areas, closely tied to human residences, and described as unique among ponerines in its seed-eating habits (Lachaud & Dejean 1994). This ant became a recognized public health hazard as its sting has resulted in few cases of fatal anaphylactic shock (Al-Anazi et al 2009). This venomous ant was abundantly found in the southern, eastern and middle regions of Saudi Arabia (Al-Khalifa et al 2010).…”
Section: Introductionmentioning
confidence: 98%